Chronic Effects of Pediatric Ear Infections on Postural Stability - Ohud A. Sabir; Eric G. Johnson; Ammar E. Hafiz; Rhonda N. Nelson; Mitali Hudlikar; Isha Sheth; Noha S. Daher (International Journal of Pediatrics)
Background. Ear infections in children often cause abnormal postural stability. However, the long-term effects of recurrent ear infections on postural stability have not been investigated. Purpose. The purpose of this study was to examine the long-term effects of multiple ear infections on pediatric postural stability. Methods. Forty children aged 10-12 years were divided into two groups (18 participants with a history of tympanostomy tubes and/or 3 or more ear infections prior to age five and 22 participants without a history of tympanostomy tubes and/or 0-2 ear infections prior to age five). Computerized Stability Evaluation Test (SET) and noncomputerized postural stability were measured for all participants. Results. A significant difference was found in median postural stability scores in the SET during a tandem stance on an unstable surface between the two groups (median (minimum, maximum) of 9.1 (1.4, 11.4) versus 5.8 (1.7, 12.8), p=0.04). In addition, there was a significant difference in median Pediatric Balance Scale scores between participants with versus without ear infection (54 (47, 56) versus 56 (55, 56), p=0.001). Conclusions. Results suggest that children ages 10-12 with a history of tympanostomy tubes and/or 3 or more ear infections prior to age five have decreased postural stability.